The Influence of Supportive Supervisory Practices and Health Care Aides' Self-Determination on the Provision of Person-Centered Care in Long-Term Care Facilities. (November 2019) - Caspar, Sienna; Le, Anne; McGilton, Katherine S.
Person-centred care (PCC) is recognized as best practice in long-term care (LTC). Using a cross-sectional design, we examined the relationship between supportive supervisory practices and health care aides' (HCAs) self-determination on HCAs' perceived ability to provide PCC. A total of 131 HCAs from four LTC facilities participated in the study. There were strong, positive associations between HCAs' self-determination and their perceived ability to provide PCC, r = .59, p < .0001, and how supportive their supervisors were, r = .50, p < .0001. Mediation analysis using structural equation modeling found the direct effect of self-determination on PCC was 73% of its total effect on PCC; its indirect effect mediated through supervisory support was 27% of its total effect on PCC. Improving supportive supervisory relationships that encourage and enable HCAs' self-determination in LTC settings may be an important and effective means by which to increase the provision of PCC.